Assessing a virtual reality display system for teleradiology purposes using the receiver operating curve methodology - Kocatürk, Eylem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
In a radiology reading room, multiple ﬂat displays are used for the comparison aspect. This approach increases the overall expense and also requires more space. So, virtual reality techniques can be applied to teleradiology. By using VR devices, radiologists may complete diagnostic tasks outside of hospital settings. In this study, 100 lung X-ray images with deﬁnite ﬁndings were gotten from the database approved by the radiologists. Five radiologists from Yeditepe University Hospital assessed these images both on a medical grade LCD monitor and on the Oculus Rift CV1. The receiver-operating characteristic (ROC) curves for all display reader cases were statistically compared to check observers’ performances. AUC for virtual reality head mounted display for reader 1, 2, 3, 4,5 and overall were calculated as 0.931, 0.865, 0.805, 0.775, 0.728 and 0.814 respectively. AUC for medical monitor were 0.948, 0.915, 0.897, 0.771, 0.769 and 0.861. Sensitivity and speciﬁcity of p values from McNemar test were 0,37 and 0.90 respectively. Since, the p values are greater than 0.05, this is a good indicator of no diﬀerence between two diagnostic techniques. Weighted kappa results for reader 1, 2, 3, 4, 5 and overall were 0.656, 0.782, 0.557, 0.383, 0.224 and 0.542 respectively. So, the overall weighted kappa value showed the moderate agreement between two diagnostic techniques.So, Oculus Rift CV1 can be used as a diagnostic display by the radiologists.
Keywords: Radiology, Medical.; Radiography.; Telecommunication in medicine